ChemInform Abstract: Synthesis of 2‐C‐Substituted Benzothiazoles via a Copper‐Promoted Domino Condensation/S‐Arylation/Heterocyclization Process. Issue 48 (2nd December 2014) - Xiang, Haoyue; Qi, Jin; He, Qian; Jiang, Min; Yang, Chunhao; Deng, Lianfu
Abstract The reaction yields are severely affected by the substituents of (I).